2021
DOI: 10.3389/fimmu.2021.706936
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related lncRNA Prognostic Signature and Molecular Subtypes for Glioblastoma

Abstract: BackgroundGlioblastoma multiforme (GBM) is extensively genetically and transcriptionally heterogeneous, which poses challenges for classification and management. Long noncoding RNAs (lncRNAs) play a critical role in the development and progression of GBM, especially in tumor-associated immune processes. Therefore, it is necessary to develop an immune-related lncRNAs (irlncRNAs) signature.MethodsUnivariate and multivariate Cox regression analyses were utilized to construct a prognostic model. GBM-specific CeRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
(60 reference statements)
1
26
0
Order By: Relevance
“…The clinical data and transcriptome data were retrieved from the TCGA database, including 1,096 BRCA specimens and 112 normal specimens. We performed Spearman correlation analysis between the lncRNAs and NRGs, and 1,520 necroptosis-related lncRNAs (NRlncRNAs) were sorted out with the filter criteria of correlation coefficients >0.4 and p < 0.001 ( 21 , 22 , 31 , 32 ) ( Table S1 and Figure 2A ). Forty-six prognostic NRlncRNAs in BRCA were extracted by univariate analysis, of which the significant filtering condition was p < 0.05 ( Table S2 and Figures 2B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical data and transcriptome data were retrieved from the TCGA database, including 1,096 BRCA specimens and 112 normal specimens. We performed Spearman correlation analysis between the lncRNAs and NRGs, and 1,520 necroptosis-related lncRNAs (NRlncRNAs) were sorted out with the filter criteria of correlation coefficients >0.4 and p < 0.001 ( 21 , 22 , 31 , 32 ) ( Table S1 and Figure 2A ). Forty-six prognostic NRlncRNAs in BRCA were extracted by univariate analysis, of which the significant filtering condition was p < 0.05 ( Table S2 and Figures 2B, C ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a large scale of bioinformatics studies utilized public data resources to identify glioma prognostic signatures, including gene signatures ( 35 40 ), lncRNA signature ( 41 ), and gene-set signature ( 42 , 43 ). The summary of all of these prognostic studies and our study was displayed in Table S4 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the differences in KRT8 expression between PDAC and normal pancreas tissue were statistically significant (Figures 3(a) – 3(d) ). Recent studies revealed that the overexpression of KRT8 could be also found in glioblastoma [ 43 ]. Interestingly, Nordgård et al found that KRT8 was upregulated in the bone marrow aspirates from advanced PDAC patients, possibly caused by infiltrated PDAC cells, indicating the potential role of KRT8 in the formation of tumour microenvironment [ 44 ].…”
Section: Discussionmentioning
confidence: 99%